Response of Kochia plant ( Kochia scoparia L.) to some chemical and bio fertilizer treatments - Salma Sayed Ahmed Abdelfatah Abulmagd; Aboudahab Mohamed Aboudahab; Faisal Mohamed Saadawy; Samia Sami Helme (Cairo : Salma Sayed Ahmed Abdelfatah Abulmagd, 2016)
Two experiments were carried out on Kochia scoparia plants at the nursery of the Department of Ornamental Plants, faculty of Agriculture, Cairo University in two seasons 2013 and 2014. In the first experiment, plants grown in 30 cm plastic pots filled with clay soil were treated with different levels and combinations of Ammonium Sulphate, Nitrobein and Phosphorein. In the second experiment, plants grown in similar pots filled with sand and peat moss (at 3:1 v:v.) were treated with different levels and combinations of Nitrobein, Phosphorein and Rock phosphate. Results showed that briefed in the following: Experiment 1: Plants were treated with Ammonium Sulphate (3g/pot) gave the tallest plants. Plants were treated with Nitrobein (2 g/pot) gave the highest value of plant circumference. Plants were treated with Ammonium Sulphate (6 g/pot) + Nitrobein (2 g/pot) + Phosphorein (2 g/pot) gave the highest values of fresh and dry weights of shoots, the highest content of chlorophyll "a, b, total chlorophylls" and the highest contents of carotenoides. Plants were treated with Phosphorein (3 g/pot) gave the highest value of total carbohydrates%. Plants were treated with Ammonium Sulphate (9 g/pot) + Nitrobein (3 g/pot) + Phosphorein (3 g/pot) gave the highest content of nitrogen%. Plants were treated with Nitrobein (3 g/pot) gave the highest content of phosphorus%. Plants were treated with Ammonium Sulphate (9g/pot) or Nitrobein (2 g/pot) gave the highest content of potassium%.
Thesis (M.Sc.) - Cairo University - Faculty of Agriculture - Department of Ornamental Horticulture
Issued also as CD
Keywords: Ammonium Sulphate; Kochia scoparia; Phosphorein and Rock Phosphate